The Role of Al-khairaat Media as a Channel Communication of Da'wah in Palu City - Suharto, S.; Abu, Ardillah; Hamsah, Muhammad (Golden Ratio of Social Science and Education, 2022)
This article aims to find out how the existence of alkhairat media and its role as a da'wah communication channel in the city of Palu. This study used qualitative research methods. The type of data to be collected in this study consists of primary data and secondary data. The primary data in this study were in the form of words or verbal utterances and the behavior of the subject or research informant related to the Alkhairat Media in the city of Palu. The primary data of this study were sourced from informants who were directly related and knew clearly about the problems studied, namely the editors of the Media Alkhairat daily newspaper, Palu City and stakeholders in the city of Palu. While secondary data is data sourced from documents in the form of notes, reports and other forms of documents. Data collection techniques in this study using observation and interview techniques. data analysis techniques using data reduction techniques, data presentation and data verification. The results of this study indicate that the existence of alkhairaat media as a propaganda channel in the city of Palu has the main characteristics, namely; Editorial guide policy Prioritizing local content enriched with regional content, national content, international content, Da'wah content that is more inclusive, tolerant, washatiyah and moderate, has a vision for alkhairaatan as a means of education and empowerment of the community and has a semi-Republican style, meaning mainstream content, but cannot be separated from the corridor of Islamic values. The role of Media Alkhairaat as a propaganda channel in the city of Palu is as a communicator, motivator, reference source and public education.